Genetic diversity, growth effecting factors and nutritional value of moringa - Rufa'i, Shamsuddeen (2016)
Taking into account the various cases of malnutrition affecting many impoverished nations of the developing world, the current research effort was conceived with the objective of appraising the nutritive potential of „Moringa‟ (Moringa oleifera L.) plant through the evaluation of proper agronomic practice that will enhance its nutritive potential. Various accessions were first tested for genetic diversity using RAPD markers; afterwards, growth and development pattern were determined through the assessment of the effect of applied phosphorus (P) and potassium (K) nutrient levels on the „Moringa‟ performance. Applications of 5 levels of P and K revealed significant variations for plant height, stem diameter, crop growth rate (CGR), relative growth rate (RGR), net assimilation rate (NAR), leaf area index (LAI), SPAD chlorophyll content, root length, root volume, root diameter, stem dry weight, leaf dry weight, root dry weight, and total dry matter (TDM). Average values of 0.279 g cm-2 day-1, 0.029 mg g-1 day-1, and 0.149 g cm-2 day-1 were obtainedfor CGR, RGR, and NAR, respectively. The LAI values ranged from 1.43 to 2.13, while TDM values varied from 17.36 to 22.17 g plant-1. Evaluating measuredquantity of dried roots, stem, and leaves portions for essential and non-essential amino acids content through high-performance liquid chromatography (HPLC) analysis revealed the presence of 9 essential and 7 non-essential amino acids, with a range of 4.24 to 10.04 g kg-1 recorded for leucine, threonine, histidine, glutamic acid, aspartic acid, and glycine. The 2,2ꞌ- diphenyl-1- picrylhydrazyl (DPPH) and theferric reducing antioxidant power (FRAP) assay revealed strong antioxidants presence (up to 68% DPPH scavenging activity) and a high level FRAP potential of 2500 mg ascorbic acid equivalent (AAE) / 100 g dry weight (DW). Folin-Ciocalteu‟s and aluminium chloride calorimetric assay revealed high levels of secondary metabolites (ranging from 1000 – 1350 mg gallic acid equivalent (GAE)/100 g DW total phenolics and up to 2400 mg quercetin equivalent (QE)/1 mg DW total flavonoids), and the wet digestion procedure revealed the presence of 9 mineral nutrient elements (with significant values of up to 19.13 g kg-1 maximum)content acquired from calcium (Ca) and up to 9.90 g kg-1 recorded for iron (Fe).These nutritive components are noted to be highest (312.5% higher in terms of antioxidants) in the leaves portion, followed by the roots, and then the stem parts. Influence of growth media, stem diameter, and growth regulators were evaluated using two growth media (with and without biochar) and three levels of indole 3-butyric acid (IBA). Plant height, percentage of primary branch produced, leaf area, and dry matter (DM) were found to be significantly (P<0.05) influenced by variation in stem diameter magnitude. The use of 2 growth media (munchong series soil [M] and munchong series soil mixed with Biochar [MB]) revealed a significant influence of the MB growth media on plant height, percentage root number, and root length as compared to the M growth media, but the trial record no significant variation in growth parameters in terms of IBA applications on the stem cuttings.